2022
DOI: 10.26434/chemrxiv-2022-9zhk2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classification of Cannabinoid Spectra Using Machine Learning

Abstract: Vibrational spectroscopy, encompassing Raman and Infrared (IR) spectroscopy, is a powerful technique that probes the intrinsic vibrations of a molecule, thus providing a unique chemical signature for that molecule. This information is beneficial to differentiate between two similarly structured molecules since their vibrational fingerprint will be different. In an effort to introduce an automated spectroscopic data analysis tool, we explore different Machine Learning (ML) algorithms to identify the chemical st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…This method reduces noise while maintaining the shape and height of waveform peaks [50,51]. Prior studies have demonstrated the effectiveness, particularly when combined with machine learning models [59,11,26]; nevertheless, it is imperative to acknowledge two inherent limitations associated with SG-őlters: (1) their typical application assumes equidistant data points, and (2) operations near the boundaries of the data range are prone to artifacts, particularly pronounced when employed for derivative calculations. The őrst limitation is solved by the application of linear interpolation, as mentioned earlier.…”
Section: Noise Reduction and Normalizationmentioning
confidence: 99%
“…This method reduces noise while maintaining the shape and height of waveform peaks [50,51]. Prior studies have demonstrated the effectiveness, particularly when combined with machine learning models [59,11,26]; nevertheless, it is imperative to acknowledge two inherent limitations associated with SG-őlters: (1) their typical application assumes equidistant data points, and (2) operations near the boundaries of the data range are prone to artifacts, particularly pronounced when employed for derivative calculations. The őrst limitation is solved by the application of linear interpolation, as mentioned earlier.…”
Section: Noise Reduction and Normalizationmentioning
confidence: 99%